Emotional exhaustion health professionals and their association with interventing variables (Research, Society and Development, 2020)
Objective: To analyze the association between the variable emotional exhaustion and individual, labor and behavioral variables. Method: Cross-sectional, descriptive and correlational study, among 282 health professionals from emergency services, in the city of Ribeirão Preto, SP, Brazil. The following instruments were used: Sociodemographic Questionnaire, Maslach Burnout Inventory, Childhood Trauma Questionnaire, Stress Symptoms Inventory, Perceived Stress Scale, Psychiatric Screening Questionnaire, Fantastic Lifestyle Questionnaire, Hospital Anxiety and Depression Scale and Homes-Rahe Social Readjustment Scale. Descriptive writing of data and Pearson's Chi-Square or Fisher's Exact tests to verify the association between variables and later regression analysis. Results: There was statistical evidence of an association between Emotional Exhaustion and schooling, use of psychiatric drugs, early stress, stress, common mental disorders, lifestyle, anxiety, depression and social readjustment. After regression analyzes, the correlations with: education, use of psychiatric drugs, absence from work, common mental disorders and social readjustment remained evident. Conclusions: It was evidenced that a significant part of professionals working in urgent and emergency services are affected by Emotional Exhaustion. This study points to a profile for the development of Emotional Exhaustion, made up of health professionals with higher education, who use psychotropic drugs, who have already been away from work in the last year, who show symptoms of mental suffering and social readjustment.